2005
DOI: 10.1038/ncb1221
|View full text |Cite|
|
Sign up to set email alerts
|

Maintenance of the diacylglycerol level in the Golgi apparatus by the Nir2 protein is critical for Golgi secretory function

Abstract: The level of diacylglycerol (DAG) in the Golgi apparatus is crucial for protein transport to the plasma membrane. Studies in budding yeast indicate that Sec14p, a phosphatidylinositol (PI)-transfer protein, is involved in regulating DAG homeostasis in the Golgi complex. Here, we show that Nir2, a peripheral Golgi protein containing a PI-transfer domain, is essential for maintaining the structural and functional integrity of the Golgi apparatus in mammalian cells. Depletion of Nir2 by RNAi leads to substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 49 publications
7
135
0
Order By: Relevance
“…DAG-mediated PKD activation regulates vesicle budding and fission from the TGN, a process negatively regulated by DGK. 16,19,65 Our results here identify an additional PKD1/2 function as a major downstream effector of DGKα in the control of MVB traffic and exosome secretion in T and B cells. DGKα-mediated DAG consumption limits PKD subcellular location and activation in T ymphocytes during IS formation.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…DAG-mediated PKD activation regulates vesicle budding and fission from the TGN, a process negatively regulated by DGK. 16,19,65 Our results here identify an additional PKD1/2 function as a major downstream effector of DGKα in the control of MVB traffic and exosome secretion in T and B cells. DGKα-mediated DAG consumption limits PKD subcellular location and activation in T ymphocytes during IS formation.…”
Section: Discussionmentioning
confidence: 58%
“…[10][11][12][13][14][15] The discovery of exosome involvement in these responses increased interest in the regulation of exosome biogenesis and secretory traffic, with special attention to the contribution of lipids such as ceramide and DAG, as well as DAG-binding proteins. 14,[16][17][18][19][20][21] These studies suggest that positive and negative DAG regulators may control secretory traffic. By transforming DAG into phosphatidic acid (PA), diacylglycerol kinase α (DGKα) is essential for the negative control of DAG function in T lymphocytes.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The corresponding proteins have an important role in phospholipid biosynthesis. 38 Some of these changes are expected to have an effect on the synthesis of HDL. 39 Effect of fenofibrate on genes affecting triglyceride hydrolysis, FA transport, b-oxidation, other mitochondrial function, fatty acid biosynthesis and carbohydrate metabolism The monoglycerides generated by the actions of Lpl and Pnliprp, which are upregulated, can be channeled toward phospholipid biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the overexpression of Chka will promote phosphocholine biosynthesis and the overexpression of Pitpnm1, which regulates DAG consumption via the CDP-choline pathway, may promote phosphatidylcholine biosynthesis. 38 A previous study showed that the biosynthesis of phosphatidylcholine in the liver is important for HDL formation. 39 Overall, the upregulation of the genes involved in phospholipid biosynthesis as well as that of Lpl may account for the observed increase in HDL levels, and the modest downregulation of the Srb1 gene may account for the increase in the size of HDL in response to fenofibrate treatment.…”
Section: Discussionmentioning
confidence: 99%